Extracting triples from web document / Nur Afiqah Mazlan - Mazlan, Nur Afiqah (2014)
Nowadays Semantic Web technologies become a most popularity in the world. According to Berners-Lee, he said that a web of data that can be processed directly and indirectly by machines. In the world, all human need the information and they can search information through internet. But when the process of searching for specific information become more complex, it is very hard to minimize the number of unrelated documents for the output specific searching. Therefore, the meaning of the sentences is ignored and no extraction or annotation tasks are involved. This research will be use the technique of Semantic Web to convert web document into triples. Semantic Web uses the triples data or RDF data to reduce the unrelated document only exactly document will be post in internet. Next Semantic Web also can be used to evaluate the effectiveness from of match triples from given a query. This research used collection a web document of durian for data collection to show that the effectiveness triples of match from given a query. This research can show the performance of the document when the data of durian convert to triples. In semantic web, the user can search the durian data more efficiency and effectiveness because, the Semantic Web is more flexible data model and make the data independent of its internal representation.